ACRITARCHS FROM UPPER BEDS OF THE UPPER CAMBRIAN-LOWER TREMADOCIAN OF THE MOSCOW SYNECLISE - Volkova N.A. (My University, 1999)
The Cambrian-Ordovician boundary beds of the Moscow syneclise contain three acritarch assemblages; one of them is from the uppermost part of the Upper Cambrian (UC4B-1) and the other two from the lower Tremadocian (OT1 and OT2). In taxonomy, the studied assemblages are similar to those of the lower Tremadocian in the Peri-Gondwana cold-water province owing to the climatic cooling of that time.
Keywords: Cambrian; Tremadocian; Палеозой::Кембрийская; Paleozoic::Ordovician::Lower::Tremadocian; Paleozoic::Cambrian; Палеозой::Ордовикская::Нижний::Тремадокский